Komunikasi Interpersonal dalam Hubungan Jarak Jauh (Long Distance Relationship) pada Mahasiswa Universitas Singaperbangsa Karawang di Luar Pulau Jawa - Ramdhan, Muhammad; Ema, Ema; Oxcygentri, Oky (CV. ULIL ALBAB CORP, 2025)
This study aims to determine the forms of interpersonal communication used by Long-Distance Relationship (LDR) couples and the challenges faced in maintaining these relationships among students at Singaperbangsa University, Karawang. This study used a qualitative approach with a descriptive study method. The informants in this study were four LDR couples consisting of male and female students in long-distance relationships. Data collection techniques were carried out through in-depth interviews and documentation. The results showed that the form of interpersonal communication most frequently used by LDR couples was digital technology-based communication, such as chat, telephone, and video calls through applications such as WhatsApp, Google Meet, and Zoom. Communication was carried out regularly with the aim of maintaining emotional closeness and avoiding misunderstandings. In addition, the couples also demonstrated openness, honesty, and a high level of commitment as part of a strategy to maintain relationship quality.